Legal Protection for Disabilities Persons with Language Limitations in Law Enforcement - Vera Bararah Barid; Dewi Analis Indriyani; Yeni Yulianti; Sri Gilang Muhammad Sultan Rahma Putra; Penny Naluria Utami (Jurnal HAM, 2022)
The Indonesian government has enacted various regulations aimed at protecting individuals with disabilities, yet significant gaps persist in their implementation. Discrimination against people with disabilities, particularly those with language impairments, remains prevalent, especially within the legal system. This study employs a sociolegal approach to examine the challenges faced by disabled individuals with language limitations in accessing legal protection. Key aspects analyzed include existing regulatory frameworks for disability protection, case studies of legal decisions involving disabilities, the handling of legal proceedings, challenges encountered by stakeholders in legal cases, and the impact of limited access to sign language and legal knowledge. The research reveals that individuals with hearing impairments often struggle to exercise their rights to assistance from sign language interpreters during legal proceedings. This deficiency is primarily attributed to a lack of awareness and understanding among various stakeholders regarding the specific needs of people with hearing impairments. Furthermore, the effectiveness of law enforcement processes for disabled individuals is hindered by regional variations in sign language, the existence of informal or non-standardized sign languages, and the limited proficiency of law enforcement personnel in communicating with and accommodating individuals with disabilities. In conclusion, the study underscores the urgent need for improved implementation of existing disability rights regulations in Indonesia, particularly within the legal context. Addressing these challenges requires enhancing awareness and training among legal professionals and stakeholders, ensuring consistent access to qualified sign language interpreters, and promoting standardized approaches to accommodating individuals with disabilities in legal proceedings. By bridging these gaps, Indonesia can move closer to fulfilling its commitment to upholding the rights and dignity of all individuals, including those with disabilities, within its legal system.